Dampak Rasio Keuangan terhadap Nilai Perusahaan dengan Pemoderasi Pengungkapan Corporate Social Responsibility pada Perusahaan Pertambangan Batu Bara - Anas, Hasib Hanafi; Nur, Dhani Ichsanuddin (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study investigates the relationship between profitability parameters and company size and firm value moderated by disclosure of corporate social responsibility in the coal mining sub-sector which is traded on the Indonesia Stock Exchange. The results of the study found that firm value increases with profitability, decreases significantly with firm size, profitability moderated by disclosure of corporate social responsibility has a significant negative effect on firm value, and firm size moderated by disclosure of corporate social responsibility cannot contribute to firm value. Moderate regression analysis used for data analysis in this study is Moderated Regression Analysis (MRA).